2017
DOI: 10.1016/j.tca.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior at moderate temperature under dry and wet air of phenolic resin-derived carbon

Abstract: International audienceThe oxidation behavior of carbon materials has been investigated at temperatures less than 773 K using isothermal thermogravimetric analyses under dry and wet air. Bulk samples obtained by the pyrolysis of phenolic resin have been characterized using X-ray diffraction and elementary analysis. X-ray photoelectron spectroscopy and Raman spectroscopy have been performed to analyze the surface and subsurface. The carbon structure has a poor organization state and a gradient in the oxygen conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…The evident effect of protection activity of Ce-doped lead zirconate is the delay of ageing in the favor of recombination through which the gelation occurs. This contribution was already reported for other type of materials, which are subjected to an accelerated process of degradation [20,21].…”
Section: Resultssupporting
confidence: 71%
“…The evident effect of protection activity of Ce-doped lead zirconate is the delay of ageing in the favor of recombination through which the gelation occurs. This contribution was already reported for other type of materials, which are subjected to an accelerated process of degradation [20,21].…”
Section: Resultssupporting
confidence: 71%
“…This model seems to properly explain the differences encountered with the theoretical paralinear model. Such a kind of behaviour has already been observed for oxidation in air of poorly crystallized carbon (phenolic resin-based carbon): similar layered crystalline structure, sensitive to adsorption and/or intercalation phenomena [10,11].…”
Section: Model For Wet Airmentioning
confidence: 72%
“…The results can be probably attributed to the partial collapse of some pore walls or the recession of some pore channels by the reaction related to O 2 , and eventually some micropores or/and mesopores became expanded or collapsed in different extent, resulting in the decrease of micropore volume. 39,40 However, when the preoxidized carbon spheres are subjected to the ammonia thermal treatment under 800 C, the oxygen surface groups rstly give rise to decomposition that creates the vacant Table 1 Porous structure parameters of the samples a sites in the pores, which provide more opportunities to increase reaction probability with created free radicals under the simultaneous ammonia treatment at 800 C. It has been also reported that gasication with ammonia has a protable to recover its porosity blocked by preoxidization, and increase the porous structure parameters over that of the oxidized sample. 41,42 Moreover, the carbon spheres (ACSON) obtained by the preoxidation-assisted ammonia thermal treatment show bigger BET surface, total pore volume and microporous volume than those of the direct oxidized carbon spheres.…”
Section: N 2 Adsorption-desorption Analysismentioning
confidence: 99%
“…2(e), although it maintains good sphericity. The phenomenon can be attributed to the synergistic effect of thermal air oxidation and ammonia etching action, 37,39 in which the surface oxygen functional groups to create vacant sites through thermal decomposition, and free radicals (NH 2 , NH and H) react with these vacant sites or surface oxygen functional groups to develop pore structure, leading to the increase of BET surface area and pore volume and simultaneously the introduction of nitrogen containing functional groups in the ACSON. On the contrary, CACS from commercial activated carbon is very different, the exterior surface shows some big cracks with roughness in Fig.…”
Section: Surface Morphology Analysismentioning
confidence: 99%
See 1 more Smart Citation